Tafsiran Kognisi Puitis Terhadap Lagu Black Brothers Dalam Mengungkap Transkrip Tersembunyi (Hidden Transcript) - Awom, Iriano Yedija Petrus (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
This research attempts at analyzing some selected songs of Black Brothers, a legendary popular band of Papua, using hidden transcript theory by James Scott. In avoiding direct retaliation with the ruling tyrant somehow some people would employ safer way in making criticism. This form of passive and peaceful resistance is disguised and veiled through witty symbolism and linguistic trick such as metaphorical expression, euphemism, folktales, and anonymity. Therefore, in order to understand and unveil the intended message behind those disguises, one has to make a careful reading. And to have a good undertanding of hidden transcript in Black Brothersâ songs hopefully can raise peopleâs sense of humanityand can stand up for truth and for their right.